LEARNING DISABILITY AND SPEECH DISORDER AMONG TODDLERS: A CASE STUDY ON KURDISH PRE-SCHOOL CHILDREN - Areen Ahmed Muhammed (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
For decades, scholars and linguists in Iraqi Kurdistan studied on University students. However, a few types of research could be found in the area of language disability among Kurdish children. This research tried to clarify and illustrate the impact of those factors that have the main role in enhancing children and evoke them while they are in the phase of learning to talk. It also tried to show disorders as infants have, and to find out the most effective factor, which helps infants to learn to talk soon. The participants in this research were teachers at two different primary schools in Sulaymaniya. Moreover, two methods of data collection were used in this study (questionnaire and interview). Additionally, thirty teachers took part in the questionnaire; additionally, fifteen teachers took part in the demographic section and three mothers in the interview section. The finding of this research showed that toddlers had positive views about the effect of reading stories by their parents. They found that it was helpful for toddlers. In addition, the effectiveness of parents’ role on children`s talking was found out in this research. On the other hand, the impact of genders on infants was also carried out in this study. The most important finding of this research was the effectiveness of telling the original names of items to infants by their parents. In addition, mothers could positively enhance the children’s ability to talk and learn sooner than those whose parents did not talk to them much or they had quiet parents.